Decentralization, local governance, and local economic development in Mongolia. - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
In Mongolia, the legal, institutional, and fiscal environment in which local governments operate, provides several constraints and opportunities that impact on that role. In this publication, we assess both the formal features of Mongolia's system of decentralized governance and the way that system works in practice. We also provide practical suggestions for improvements to the current system.
Keywords: Decentralization in management; Decentralization in management -- Mongolia; Electronic book